Upaya Pencegahan Tuberculosis melalui Edukasi di Puskesmas Ciawigebang Kabupaten Kuningan - Sipa Febiyanti; Risna Nurlia; Seila Azmia; Nur Laily Ramdahani; Fadli Nur Fachrozi (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The high prevalence of Tuberculosis (TB) within the operational area of the UPTD Ciawigebang Community Health Center served as the impetus for conducting Field Learning Practice (PBL) II which aimed to identify the causes of the issue and devise prevention measures. This community service activity aimed to analyze TB cases, determine the contributing factors, and design suitable health promotion interventions. The methods employed included community education via outreach using leaflets, problem prioritization using the Urgency, Seriousness, and Growth (USG) method, root cause analysis (fishbone), and the formulation of alternative solutions implemented through the Plan-Do-Check-Act (PDCA) approach. The findings revealed that limited public knowledge and low awareness of early health examinations were the primary factors contributing to the high incidence of TB. Health education through counseling sessions and leaflets proved to be an important strategy for improving community awareness and supporting sustainable TB prevention and control efforts.